Associations between migrant status and sexually transmitted infections among female sex workers in Tijuana, Mexico. Issue 6 (2nd February 2009) - Ojeda, V D; Strathdee, S A; Lozada, R; Rusch, M L A; Fraga, M; Orozovich, P; Magis-Rodriguez, C; De La Torre, A; Amaro, H; Cornelius, W; Patterson, T L
Abstract : Objective: To examine associations between migration and sexually transmitted infection (STI) prevalence among Mexican female sex workers (FSW). Methods: FSW aged 18 years and older in Tijuana, Baja California (BC) underwent interviews and testing for HIV, syphilis, gonorrhoea and chlamydia. Multivariate logistic regressions identified correlates of STI. Results: Of 471 FSW, 79% were migrants to BC. Among migrant FSW, prevalence of HIV, syphilis, gonorrhoea, chlamydia and any STI was 6.6%, 13.2%, 7.8%, 16.3% and 31.1% compared with 10.9%, 18.2%, 13.0%, 19.0% and 42.4% among FSW born in BC. A greater proportion of migrant FSW were registered with local health services and were ever tested for HIV. Migrant status was protective for any STI in unadjusted models (unadjusted odds ratio 0.61, 95% CI 0.39 to 0.97). In multivariate models controlling for confounders, migrant status was not associated with an elevated odds of STI acquisition and trended towards a protective association. Conclusions: Unexpectedly, migrant status (vs native-born status) appeared protective for any STI acquisition. It is unclear which social or economic conditions may protect against STI and whether these erode over time in migrants. Additional research is needed to inform our understanding of whether or how geography, variations in health capital, or social network composition and information-sharing attributes can contribute to health protective behaviours in migrant FSW. By capitalising on such mechanisms, efforts to preserve protective health behaviours in migrant FSW will help control STI in the population and may lead to the identification of strategies that are generalisable to other FSW.